ConRec: An Ontology-Based Recommender System for Concept Coverage in Education Enhanced with a Gamified Chatbot Interface - Belizário Júnior, Clarivando F.; Dorça, Fabiano A.; Assis, Luciana; Vivas, Alessandro; Cattelan, Renan G.; Souza, Arthur H. de (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2025: Anais do XXXVI Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2025.12799, 2025)
This paper presents an improvement to ConRec, an ontology-based recommender system designed to personalize learning by ensuring concept-level coverage of educational content. The system models students and learning objects using an ontology enriched with pedagogical metadata and SWRL inference rules. To enhance usability and engagement, a gamified chatbot interface was integrated into the system. The solution was evaluated in a real classroom with Computer Science undergraduates, demonstrating high satisfaction levels, increased student engagement, and improved effectiveness in supporting learning and clarifying conceptual doubts.